Digital finance, environmental regulation, and green development efficiency of China - Han, Yaqing; Li, Yushui; Wang, Qiangqiang (Frontiers in Environmental Science, 2023)
In the context of the increasingly prominent contradiction between economic development and ecological environment, how to promote green development has become the core of sustainable economic development. Digital finance is an innovative financial model with a high degree of integration of finance and digital technology and provides a new opportunity for achieving green development. Based on identifying the mechanisms of digital finance and environmental regulation on green development efficiency, this research uses the directional distance function and Malmquist-Luenberger index to measure the green development efficiency of 30 provinces in China from 2011 to 2020 and then employs a dynamic panel GMM model to empirically analyze the relationships among digital finance, environmental regulation, and green development efficiency. The results of the study show the following. 1) Digital finance contributes to the efficiency improvement of green development. 2) Environmental regulation has not yet crossed the Porter’s inflection point and still has a dampening effect on green development efficiency. 3) The synergy between digital finance and environmental regulation has a positive impact on green development. 4) Digital finance alleviates the financing constraints arising from environmental regulation and to some extent weakens the negative effect of environmental regulation on the efficiency of green development. In view of this, the government should give full play to the active role of digital finance in eco-environmental governance, optimize the top-level design of environmental regulation, and promote industrial structure upgrading and optimal allocation of financial resources.